Α case of Yersinia pseudotuberculosis infection in canaries - IORDANIDIS (Π. ΙΟΡΔΑΝΙΔΗΣ), P.; GEORGOPOULOU (Ι. ΓΕΩΡΓΟΠΟΥΛΟΥ), I.; BOUGIOUKLIS (Π. ΜΠΟΥΠΟΥΚΛΗΣ), P.; LEKKAS (Σ. ΛΕΚΚΑΣ), St.; KOUTSOPOULOS (Δ. ΚΟΥΤΣΟΠΟΥΛΟΣ), D. (Journal of the Hellenic Veterinary Medical Society, 2017)
This study describes the diagnosis, treatment and sanitary procedures in canaries and other cage-birds in a pet-shop, infected by Yersinia pseudotuberculosis. Main macroscopic lesions in the liver, spleen and intestine were characterized by numerous nodules, from pin-head size up to a litde larger. Also, swelling of the liver and spleen and congestion with ulceration of the mucus of the intestine were observed. Parenchyma of the liver and spleen, as well as in the intestinal wall, numerous small or larger cluster-shaped colonies of Gram-negative coccobacteria were found with coagulative necrosis of the normal tissue in the development areas of the bacterium, as well as around them. Bacteriological examination from the internal organs confirmed and identified the bacterium Yersinia pseudotuberculosis. Pseudotuberculosis was established for the first time in Greece through this study. The therapeutic schema with enrofloxacin in dose of 150 mg/L in drinking water showed itself to be more effective in the first stages of the disease in other cage-bird species, but less so in canaries.